Efficacy and safety of a new generation von Willebrand factor/factor VIII concentrate (Wilate®) in the management of perioperative haemostasis in von Willebrand disease patients undergoing surgery - Windyga, Jerzy; Depka-Prondzinski, Mario von; the European Wilate Study Group; on behalf of (Thrombosis and Haemostasis, 2011)
The aim of this study was to assess the efficacy of Wilate®, a new generation, plasma-derived, high-purity, double virus-inactivated von Willebrand factor (VWF) and factor VIII (FVIII) concentrate (ratio close to physiological 1:1) in the perioperative management of haemostasis in von Willebrand disease (VWD). Data for VWD patients who received Wilate® for perioperative management were obtained from four European, prospective, open-label, non-controlled, non-randomised, multicentre phase II or III clinical trials. A total of 57 surgical procedures were performed (major: n = 27; minor n = 30) in 32 patients. The majority of patients (n = 19, 59.4%) had type 3 VWD, 9 (28.1%) had type 2 VWD and four (12.5%) had type 1 VWD. During major surgery, median daily FVIII dose and mean number of infusions were 25 IU•kg-1 FVIII (VWF:RCô23 IU•kg-1) and 11.0, respectively. Corresponding values for minor surgery were 35 IU•kg-1 (VWF:RCo ~32 IU•kg-1) and 1.5. The efficacy of Wilate® was rated by the investigator as excellent or good in 51 of 53 (96%) procedures. Tolerability was rated as very good or good in 100% of major surgeries (27 of 27) and minor surgeries (29 of 29). Wilate® is an effective and well-tolerated VWF/FVIII replacement therapy in the perioperative management of haemostasis in patients with VWD. It can be administered at a similar FVIII dose, but at a lower VWF dose, as compared to older generation products. Clinical benefits were shown in a population with a high proportion of type 3 VWD patients.
Keywords: Factor VIII; surgery; von Willebrand disease; von Willebrand factor; Wilate®